Effect of lanthanum doping on tetragonal-like BiFeO3 with mixed-phase domain structures - You, Lu (2014)
The recent discoveries of both chemical-driven and strain-driven morphotropic phase boundaries (MPBs) in BiFeO3 (BFO) thin films have opened up new horizons in developing high-performance lead-free piezoelectrics. An attempt to bridge these two MPBs is made by doping La into highly strained BFO thin films with the coexistence of tetragonal-like and rhombohedral-like phases. The structural, morphological, and ferroelectric properties of such films are investigated. It is observed that La doping changes the energy landscape between the tetragonal-like and the rhombohedral-like polymorphs due to the chemical pressure imposed by the La substitution. Polar instability is found upon increasing La doping for the in-plane polarization component, which correlates with the vanishing of in-plane ferroelectric domain structures. The transition sequence of the in-plane ferroelectric polarization resembles that previously reported for the bulklike rhombohedral phase of BFO under continuous La doping, indicating the universality of the chemical-alloying effect on the ferroelectric order.